A Case Study on Roundabout under Congestion: Proposal to Improve Current Traffic Operation - Aboud, Ghufraan Mohammed; Abdulwahab, Areej Muhy; Banyhussan, Qais Sahib; Zubaidi, Hamsa Abbas (Salehan Institute of Higher Education, 2019)
Roundabouts are progressively being utilized on occupied arterial streets for traffic quieting purposes. Be that as it may, on the off chance that one indirect leg is close to a conveyance center point, for instance, stopping territories of strip malls, the passage traffic volumes will be especially high in pinnacle hours. On the basis of the Al-Turkman Roundabout, which is one of the most important roundabouts in Baghdad city, linking the areas of east of Baghdad to the city center in the area of Bab Al-Moatham. This area is characterized by its high traffic volumes (congestion), especially at peak periods causing a low level of service (LOS) with increased travel time delay, costs, and CO2 emissions. The research relied on the use of the SIDRA software to assess these variables by collecting traffic volumes in this area. The research proposed a series of planning procedures which are divided according to serial time scales. These planning procedures are to address the problem of congestion and traffic jams in the area, improve the level of service, and reduce travel time, cost and CO2 emissions. The research concluded that the application of the planning proposals in the study area has improved the level of service from E and F to C, reduced travel time by 16%, reduced costs by 25% and reduced CO2 emissions by 29%.